Efficacy of canakinumab in patients with Still’s disease across different lines of biologic therapy: real-life data from the International AIDA Network Registry for Still’s Disease - Vitale, Antonio; Caggiano, Valeria; Sfikakis, Petros P.; Dagna, Lorenzo; Lopalco, Giuseppe; Ragab, Gaafar; La Torre, Francesco; Almaghlouth, Ibrahim A.; Maggio, Maria Cristina; Sota, Jurgen; Tufan, Abdurrahman; Hinojosa-Azaola, Andrea; et al. (Frontiers in Medicine, 2023)
The effectiveness of canakinumab may change according to the different times it is used after Still's disease onset. This study aimed to investigate whether canakinumab shows differences in short-and long-term therapeutic outcomes, according to the different biologic treatment lines used. Patients included in this study were retrospectively enrolled from the AutoInflammatory Disease Alliance (AIDA) International Registry dedicated to Still's disease. Seventy-seven (51 females and 26 males) patients with Still's disease were included in the present study. Thirty-nine (50.6%) patients underwent canakinumab as a first-line biologic agent, and the remaining 38 (49.4%) patients were treated with canakinumab as a second-line biologic agent or with more biologic agents. No statistically significant differences were found between patients treated with canakinumab as a first-line biologic agent and those previously treated with other biologic agents in terms of the frequency of complete response (p=0.62), partial response (p=0.61), treatment failure (p>0.99), and frequency of patients discontinuing canakinumab due to lack or loss of efficacy (p=0.2). Eighteen (23.4%) patients experienced disease relapse during canakinumab treatment. Nine patients were treated with canakinumab as a first-line biologic agent, and nine patients were treated with a second or more biologic agents. No differences were found in the frequency of glucocorticoid use (p=0.34), daily glucocorticoid dosage (p=0.47), or concomitant methotrexate dosage (p=0.43) at the last assessment during canakinumab treatment.Canakinumab has been proven to be effective in patients with Still's disease, regardless of its biologic treatment line.